Comparing intentional and unintentional poisoning among patients presenting to the emergency department at a tertiary care center in Lebanon: A retrospective descriptive analysis - Alondra Barakat; Youssef Salam; Nadim Oueidat; Zyad Saifi; Hani Tamim; Ziad Kazzi; Eveline Hitti; Tharwat El Zahran (PLoS ONE, 2026)
Introduction Poisoning is a significant global public health issue, contributing substantially to emergency department (ED) visits. In 2021, the WHO reported nearly 2 million deaths and 53 million disability-adjusted life-years (DALYs) lost due to chemical exposures. Although regional data exist, Lebanon lacks national statistics on intentional and unintentional poisonings. This study compares these exposures in terms of patient characteristics, exposure agents, ED management, outcomes, and disposition. Methods A retrospective chart review was performed using a toxicology database at a tertiary care center in Beirut from March 1, 2015, to August 1, 2023. All patients presenting with poisoning were included. Variables collected included demographics, psychiatric history, exposure route and type, ED course, and clinical outcomes. Results Of 886 cases, 56.2% were intentional and 43.8% unintentional. Females predominated in intentional cases (68.3% vs. 47.9%, p < 0.001). Children under 6 years accounted for most unintentional exposures (0% vs. 48.5%, p < 0.001), while adults aged 20–59 were more often involved in intentional poisonings (69.9% vs. 31.2%, p < 0.001). Intentional exposures commonly involved sedatives, hypnotics, and antipsychotics (32.1%), while unintentional ones included analgesics (8%) and cleaning agents (7.5%). Mood disorders were reported in 45.6% of intentional cases. More patients were discharged from the ED in the unintentional group (50% vs. 38.4%, p < 0.001). Minor effects predominated in intentional exposures; unintentional cases more often showed no clinical effects. Moderate and severe outcomes occurred at similar rates. Discussion This study reveals a higher prevalence of intentional poisoning in Lebanon, particularly among females and individuals with psychiatric disorders. Unintentional poisonings predominantly affected children under six, often due to poor storage and lack of child-resistant packaging. The findings underscore the need for regulatory policies, public education, and psychiatric support. Conclusion Key differences between intentional and unintentional poisonings in Lebanon highlight the need for targeted preventive strategies and risk mitigation in high-risk populations.